探究游戏主题曲的歌曲字幕翻译策略 —— 以《英雄联盟》2023年全球总决赛主题曲 《GODS登神》为例 = Subtitling strategies for game theme song —— taking league of legends 2023 global finals theme song “GODS” as example - 黄裕惠 Wong, Rebecca Yu Hui (Nanyang Technological University, 2024)
《英雄联盟》（League of Legends）作为一款多人在线战斗竞技游戏，拥有庞大的玩家群体和全球范围内的影响力。除了游戏本身深受欢迎外，该游戏相关的音乐也备受关注和讨论。当中，每一赛季全球总决赛发布的主题曲有着极高的热度，不仅是音乐，更是一种音乐营销和情感共鸣的“工具”，深受了游戏玩家乃至非玩家的喜爱。 鉴于游戏主题曲的歌曲字幕翻译研究甚少，本文选择对《英雄联盟》2023年全球总决赛主题曲《GODS登神》进行文本分析及歌曲字幕翻译研究，旨在对游戏主题曲的歌曲字幕翻译提出策略与建议。 本文对《GODS登神》在YouTube和哔哩哔哩平台上载的音乐视频中的歌曲字幕翻译进行对比和分析，从“感性”、“自然性”、“韵律”和“节奏”层面节选例子讨论翻译的策略与选择。在比较分析中，本文发现YouTube的字幕翻译更倾向于采用直译的方式，译文字幕更适合让大众理解歌词字面上的含义；而哔哩哔哩的字幕翻译使用意译和改译等方式，在传达大意的同时带出了歌曲主题和游戏的内容，还保留了音乐性，使得译文和谐助于引起玩家群体的共鸣。 之后，本文运用了“功能对等”理论和“三美论”的角度来探讨两版歌曲字幕翻译的优劣，并提出游戏主题曲的歌曲字幕翻译策略和建议：一、在直译基础上适度引入意译和改译，以更好传达歌曲情感和意义，同时也能加入适当创作，增添译文艺术性和表现力；二、考虑音乐营销面向的市场需求，平衡译文中游戏元素的加入以服务玩家和非玩家的理解；三、精心选择词语，保持译文的押韵和节奏感，以传达原曲情感和保留音乐美，实现与原歌曲相似的效果。 League of Legends, as a multiplayer online battle arena game, has a huge player base and global influence. Beyond its popularity as a game, the music associated with the game also garners significant attention and discussion. Specifically, the theme song released for each season's Global Finals serves not only as music but also as powerful tools for music marketing and emotional resonance. Those songs are deeply loved by both gamers and non-gamers. Given the limited research on the subtitle translation of game theme songs, this paper chooses to conduct textual analysis and translation research on the 2023 Global Finals theme song of League of Legends, titled “GODS”, aiming to propose strategies and recommendations for translating subtitles of game theme songs. This paper compares and analyzes the translated subtitles of the song “GODS” in the music videos uploaded on YouTube and Bilibili platforms. Examples are excerpted from the perspectives of “Sense”, “Naturalness”, “Rhyme” and “Rhythm” to discuss translation strategies and choices. In the comparative analysis, this paper finds that YouTube's translated subtitles tend to use a more literal translation approach, making the subtitles more suitable for the general public to understand the literal meaning of the lyrics. On the other hand, Bilibili's translated subtitles utilizes methods such as free translation and adaptation, conveying the general meaning of the lyrics while bringing out the themes of the song and the content of the game, it also retains the musicality, making the translation harmonious and helping to resonate with the player community. Moreover, this paper employs the “Functional Equivalence” and “Three Beauties” theoretical frameworks to discuss the pros and cons of the two versions of song translations. It also proposes translation strategies and suggestions for translating subtitles of game theme songs: First, on the basis of literal translation, appropriately introduce paraphrasing and adaptation to better convey the emotion and meaning of the song, while also allowing for creative expression to enhance the artistic and expressive quality of the translation; Second, consider the demands of music marketing, balance the incorporation of game elements in translations to cater to both gamers and non-gamers; Third, meticulously select words, maintain rhyme and rhythm in the translation to convey the original song's emotion and preserve its musicality, achieving a similar effect to the original song.